PERKARA PERKAWINAN, WARIS, DAN WAKAF: ANALISIS TERHADAP FENOMENA KONTEMPORER - Ali Gufron, Muhamad; Glecia Radisty, Diaz (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
Islamic family law continues to experience dynamics along with the evolving lifestyle of modern Muslim society. At the practical level, new issues arise that have not been widely discussed in depth, especially those related to digital transformation, shifts in family relations, and changes in asset ownership. Islamic family law plays an important role in regulating the social life of Muslims, particularly in matters of marriage, inheritance, and endowments. This study discusses how the implementation of Islamic family law in Indonesia is carried out through the decisions of Religious Courts, as well as how the principles of classical fiqh are adapted in the context of modern law. This study uses a juridical-normative approach with case studies of several Religious Court decisions. The results of the study show that Islamic family law is dynamic and able to adapt to social changes without abandoning sharia values.